The Bad-Shahs of Small Budget: The Small-budget Hindi Film of the B Circuit - Subba, Vibhushan (BioScope: South Asian Screen Studies, 2016)
Since the early 1990s Kanti Shah has made over a hundred and forty films which cut across genres—from badland bandit films to raging action features, from horror to erotica. He has been called the “badshah” of B grade, the “sultan” of C grade, “a man forever associated with India’s adult film industry” but remains an interesting figure because he has slipped in and out of strict categorizations, having dabbled with films that fall under all the grades—A, B, and C—if those categories apply. However, most of Shah’s films have always been cast aside as degraded cultural artifacts hidden from public view, derided, and excluded from film histories. Using first hand interviews with filmmakers Kanti Shah and his brother Kishan Shah, ethnographic material, reading through journals and archival material, this article as a narrative tracks Kanti Shah’s filmmaking journey through the informal networks of the small-budget film industry (alternatively called B grade, C grade, exploitation films, paracinema) from the late 1980s to present times.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTc0OTI3NjE2NjY4MDA5